VAT 69 Malaysia's very able troopers - Mohd. Reza Zainal; Zuraidi Ishak; Johana Hassan; DD Media Consult; AETN All Asia Networks; Perbadanan Kemajuan Filem Nasional Malaysia; Malaysia. Kementerian Penerangan Komunikasi dan Kebudayaan (Kuala Lumpur : AETN All Asia Networks and National Film Department Corporation Malaysia (FINAS), 2010)
The communist were making a second attempt to topple the ruling government after their failed bid to take control of the country during the Malayan Emergency, which lasted between 1948-1960. When the end of the first Malayan Emergency was officially declared in 1960, The Malayan Communist Party regroup, reorganized their units, and trained new guerillas. They remained a force to be reckoned with and in 1968 they rose again. This program provides a new perspective on the war against the Communist insurgance, particularly the untold story about the role of VAT 69 troopers
Produced with the participation of Ministry of Information, Communication and Culture, Malaysia and National Film Department Corporation Malaysia (FINAS)
Executive producer, Dato Abdul Nasser Abu Kassim ; story by Mohd. Redza Zainal, Dini Nawawi
Narrator, Timothy Watson
dvd format
Keywords: Communist -- Malaysia; Malaysia -- History; Malaysia -- Economic conditions